(√x2+a+x)(√y2+a+y)=a ⇔{(√x2+a+x)(√x2+a−x)(√y2+a+y)=a(√x2+a−x)(√x2+a+x)(√y2+a+y)(√y2+a−y)=a(√y2+a−y) $\begin{cases}a(\sqrt{y^{2}+a}-y)=a(\sqrt{x^{2}+a}-x) \\ a(\sqrt{x^{2}+a}+x)=a(\sqrt{y^{2}+a} -y)\end{cases}chia2vếchoarồicộngvếvớivếtađượcx+y=-x-y \Rightarrow 2(x+y)=0 \Rightarrow x=-y$
(√x2+a+x)(√y2+a+y)=a ⇔{(√x2+a+x)(√x2+a−x)(√y2+a+y)=a(√x2+a−x)(√x2+a+x)(√y2+a+y)(√y2+a−y)=a(√y2+a−y) $\begin{cases}a(\sqrt{y^{2}+a}
+y)=a(\sqrt{x^{2}+a}-x) \\ a(\sqrt{x^{2}+a}+x)=a(\sqrt{y^{2}+a} -y)\end{cases}
chia2vếchoa
rồicộngvếvớivếtađượcx+y=-x-y \Rightarrow 2(x+y)=0 \Rightarrow x=-y$